Comparative proteomic analyses of Duchenne muscular dystrophy and Becker muscular dystrophy muscles: changes contributing to preserve muscle function in Becker muscular dystrophy patients. Issue 2 (28th January 2020) - Capitanio, Daniele; Moriggi, Manuela; Torretta, Enrica; Barbacini, Pietro; De Palma, Sara; Viganò, Agnese; Lochmüller, Hanns; Muntoni, Francesco; Ferlini, Alessandra; Mora, Marina; Gelfi, Cecilia
Abstract: Background: Duchenne muscular dystrophy (DMD) and Becker muscular dystrophy (BMD) are characterized by muscle wasting leading to loss of ambulation in the first or third decade, respectively. In DMD, the lack of dystrophin hampers connections between intracellular cytoskeleton and cell membrane leading to repeated cycles of necrosis and regeneration associated with inflammation and loss of muscle ordered structure. BMD has a similar muscle phenotype but milder. Here, we address the question whether proteins at variance in BMD compared with DMD contribute to the milder phenotype in BMD, thus identifying a specific signature to be targeted for DMD treatment. Methods: Proteins extracted from skeletal muscle from DMD/BMD patients and young healthy subjects were either reduced and solubilized prior two‐dimensional difference in gel electrophoresis/mass spectrometry differential analysis or tryptic digested prior label‐free liquid chromatography with tandem mass spectrometry. Statistical analyses of proteins and peptides were performed by DeCyder and Perseus software and protein validation and verification by immunoblotting. Results: Proteomic results indicate minor changes in the extracellular matrix (ECM) protein composition in BMD muscles with retention of mechanotransduction signalling, reduced changes in cytoskeletal and contractile proteins. Conversely, in DMD patients, increased levels of several ECM cytoskeletal and contractile proteins were observed whereas some proteins of fast fibres and of Z ‐disc decreased. Detyrosinated alpha‐tubulin was unchanged in BMD and increased in DMD although neuronal nitric oxide synthase was unchanged in BMD and greatly reduced in DMD. Metabolically, the tissue is characterized by a decrement of anaerobic metabolism both in DMD and BMD compared with controls, with increased levels of the glycogen metabolic pathway in BMD. Oxidative metabolism is severely compromised in DMD with impairment of malate shuttle; conversely, it is active in BMD supporting the tricarboxylic acid cycle and respiratory chain. Adipogenesis characterizes DMD, whereas proteins involved in fatty acids beta‐oxidation are increased in BMD. Proteins involved in protein/amino acid metabolism, cell development, calcium handling, endoplasmic reticulum/sarcoplasmic reticulum stress response, and inflammation/immune response were increased in DMD. Both disorders are characterized by the impairment of N ‐linked protein glycosylation in the endoplasmic reticulum. Authophagy was decreased in DMD whereas it was retained in BMD. Conclusions: The mechanosensing and metabolic disruption are central nodes of DMD/BMD phenotypes. The ECM proteome composition and the metabolic rewiring in BMD lead to preservation of energy levels supporting autophagy and cell renewal, thus promoting the retention of muscle function. Conversely, DMD patients are characterized by extracellular and cytoskeletal protein dysregulation and by metabolic restriction at the level of α‐ketoglutarate leading to shortage of glutamate‐derived molecules that over time triggers lipogenesis and lipotoxicity.